A Review on Acupuncture Efficiency in Human Polycystic Ovary/Ovarian Syndrome - Natália M. de Oliveira; Jorge Machado; Lara Lopes; Maria Begoña Criado (Korean Pharmacopuncture Institute, 2023)
Objectives: Human Polycystic Ovary/Ovarian Syndrome (PCOS), a frequent endocrine pathophysiology among women of fertile age, is associated with woman's lifespan endocrine, metabolic and psychological implications. Long-term usage side effects of allopathic strategies and their low efficacy made complementary medicine treatments a relevant subject for these patients. The main aim of this work is to review the efficiency of the acupuncture treatment reported in the latest studies on literature regarding PCOS patients.Methods: A comprehensive literature search, in English language, about the use of acupuncture on the management of PCOS, was conducted in October 2020 using EBSCO, Cochrane, PubMed, Medline, Embase, databases for randomised and non-randomised controlled trials between 2015 and 2020 (09/2015-10/2020), following the PRISMA protocol.Results: This research led us to an analysis, according to PICOS, of six final papers selected among 178 in total. The articles addressed distinct aspects of the PCOS condition, diverse acupuncture techniques and different main and secondary outcomes in agreement to the respective main objective. According to this review, acupuncture seems to be useful for the treatment of this debilitating and chronic health condition which affects millions of women worldwide, many of them part of the workforce in their community.Conclusion: Despite of the display of these positive results addressing acupuncture treatments to manage PCOS major symptoms - whether they are reproductive, metabolic, or mental health features - more research is urgent. Randomized, double blinded controlled trials with improved quality design and following STRICTA and/or CONSORT recommendations are necessary to engage acupuncture as a standardized and scientific validated technique in PCOS condition.